THE IMPORTANCE OF THE WORK OF BADO'IUS SANOI' IN SOLVING MODERN JURISPRUDENTIAL ISSUES - Qambarov A’zam Muxammadali o‘g‘li (Bright Mind Publishing, 2025)
This study examines the jurisprudential contributions of Bado’ius Sanoi’ and evaluates their significance in addressing contemporary legal challenges. Drawing from classical legal traditions, Enlightenment-era intellectual shifts, and modern theoretical developments, Sanoi’ constructs a legal philosophy grounded in the integration of moral reasoning, contextual interpretation, and pragmatic application. His engagement with Maqāṣid al-Sharī‘ah, comparative jurisprudence, and the ethical foundations of law provides a multidimensional framework that bridges historical Islamic legal thought with modern rights-based and constitutional discourses. Through an analysis of Sanoi’s methodology, this research highlights his capacity to reconcile natural law and legal positivism, situating his work within ongoing debates on judicial discretion, minority rights, legal realism, and the harmonization of Sharia-based norms with contemporary societal needs. Case studies related to religious minority protections, family law reform, and the use of legal maxims (qawāʿid fiqhiyyah) in policy development demonstrate the practical impact of his ideas in Morocco, Indonesia, and broader legal contexts. Despite critiques regarding theoretical abstraction and limitations in applicability, Sanoi’s jurisprudential model remains influential for its adaptability, insistence on moral accountability, and emphasis on contextualized legal reasoning. The study concludes that Sanoi’s work provides an essential foundation for developing responsive and ethically grounded legal systems capable of addressing modern dilemmas such as digital rights, political judicialisation, and globalized legal conflicts. His contributions continue to shape contemporary legal scholarship and offer meaningful pathways for future reforms in theory and practice.
Keywords: Bado’ius Sanoi’, modern jurisprudence, legal theory and methodology, Maqāṣid al-Sharī‘ah and legal maxims, contemporary legal challenges, comparative and contextual jurisprudence